BizTalk 2013 EDI for health care : HIPAA-Compliant 834 (Enrollment) and 837 (Claims) Solutions - Beckner, Mark (Apress, 2014)
BizTalk 2013 EDI for Healthcare - EDI 834Enrollment Solutions eliminates the complexity anddemonstrates how to build both inbound and outbound EDI 834 processes inBizTalk server that follow the required patterns for integrations with theseexchanges. Archiving, mapping,reconstituting EDI 837 data, exception handling and advanced logging andreporting (without the need for BAM!) are all covered in enough detail to allowyou to implement your own fully functional solution. The Affordable CareAct and the requirements to integrate with state Exchanges have securedBizTalk's role with integrations within the healthcare industry. EDI 834 documents are the heart to allintegrations, dealing with enrollment and the maintenance of enrollments. In order to successfully integrate with theexchanges, companies are required to implement a number of architectural componentsthat can be daunting and complex to work through. High-quality resources for IT professional to handle these challenges are sorely needed, and this resource has been designed to provide concise solutions.